Analisis Kendala Perencanaan Belajar Tuntas di Tengah Pandemi Covid-19 oleh Guru IPS Kecamatan Karangpucung Kabupaten Cilacap - Mahmudah, Mellania Nur; Mulianingsih, Ferani (Sosiolium: Jurnal Pembelajaran IPS, 2021)
This study aims to analyze the safety factor of the application of complete learning in the midst of the Covid-19 pandemic for social studies subject teachers, Karangpucung District, Cilacap Regency This research is a qualitative research that is research based on the philosophy of positivism and finding out how to apply complete learning in several SMP/MTS, Karangpucung District, Cilacap Regency. The SMP/MTS includes SMP N 1 Karangpucung, SMP Islam Karangpucung and MTS Nurul Huda Karangpucung. The research steps included internal factors of complete learning planning. From the results of research that is too strict which is protected by social studies teachers in the application of learning amid the Covid-19 pandemic. These constraints include not having a learning tool or smartphone, a very limited quota, an unstable internet network, a lack of understanding of the material and a lack of student motivation. Communication constraints that are communicated by social studies teachers are the smallest part of students, who have the most difficulty in learning students.